2016
DOI: 10.1007/s00299-015-1926-2
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic expression of Arabidopsis L-type lectin receptor kinase genes LecRK-I.9 and LecRK-IX.1 in Nicotiana benthamiana confers Phytophthora resistance

Abstract: Key messageTransgenicNicotiana benthamianalines with constitutive expression of an Arabidopsis lectin receptor kinase gene (LecRK-I.9orLecRK-IX.1) show enhanced resistance toPhytophthorapathogens, demonstrating conserved gene functionality after interfamily transfer.AbstractIn plants, cell surface receptors mediate the first layer of innate immunity against pathogenic microbes. In Arabidopsis several L-type lectin receptor kinases (LecRKs) were previously found to function as Phytophthora resistance components… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 20 publications
0
31
0
Order By: Relevance
“…NbLRK1, interacting with INF1 in Nicotiana benthamiana via its 31 amino acid region of VIb subdomain of kinase domain, mediated INF1‐induced cell death. A most recent study showed that ectopic expression of Arabidopsis L‐type lectin receptor kinase genes LecRK‐I.9 and LecRK‐IX.1 in Nicotiana benthamiana confers Phytophthora resistance (Wang et al ., ). Lrk10, which encoded an L‐type LecRK, was cloned as candidate of the disease resistance locus Lr10 in wheat (Feuillet et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…NbLRK1, interacting with INF1 in Nicotiana benthamiana via its 31 amino acid region of VIb subdomain of kinase domain, mediated INF1‐induced cell death. A most recent study showed that ectopic expression of Arabidopsis L‐type lectin receptor kinase genes LecRK‐I.9 and LecRK‐IX.1 in Nicotiana benthamiana confers Phytophthora resistance (Wang et al ., ). Lrk10, which encoded an L‐type LecRK, was cloned as candidate of the disease resistance locus Lr10 in wheat (Feuillet et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Interestingly, ectopic expression of Arabidopsis LecRK‐VI.2 in Nicotiana benthamiana leads to enhanced resistance to bacteria (Huang et al ., ). Similarly, ectopic expression of Arabidopsis LecRK‐I.9 or LecRK‐IX.1 in N. benthamiana induces resistance to Phytophthora pathogens (Wang et al ., ). By contrast, LecRK‐V.5 negatively regulates stomatal immunity upstream of ROS biosynthesis and its function in stomatal immunity is mechanistically linked to ABA signaling (Desclos‐Theveniau et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…To date, several examples of transgenic expression of cell surface immune receptor genes resulting in enhanced disease resistance have been reported (Rodriguez‐Moreno et al ., ). Although transgenic expression of such receptors enhanced disease resistance, in some cases it also has adverse effects on plant fitness, such as growth retardation or leaf necrosis (Bouwmeester et al ., , ; Wang et al ., ). In this study, we observed that expression of tomato Ve1 in tobacco caused stunted growth (Figures and S1).…”
Section: Discussionmentioning
confidence: 97%
“…Samsun. Transformation was performed by the leaf disc method as previously described (Wang et al ., ). The generated plantlets were transferred to half‐strength MS medium containing 200 mg/L kanamycin to allow root development.…”
Section: Methodsmentioning
confidence: 97%